Warfarin: time in therapeutic range, a single centre study on patients using warfarin for stroke prevention in non-valvular atrial fibrillation and prosthetic heart valves - Sadhabariss, D.; Brown, S.L. (SA Heart Journal, 2021)
Background: Two common indications for oral anticoagulants are patients with non-valvular atrial fibrillation (AF) or prosthetic heart valves (PHV). The degree of anticoagulation is monitored by evaluating the international normalised ratio (INR); however, the quality of anticoagulation, determined by the time in therapeutic range (TTR), is less often evaluated. TTR has significant clinical implications in patient outcomes. Objectives: We sought to identify the indications for anticoagulation and determine its quality via the TTR at a single centre, community-based and district level hospital in the setting of usual care. We documented the prevalence of thrombo-embolic and haemorrhagic adverse events and we also collected data on factors that may contribute to a poor TTR or increased risk of adverse events. Methods: We conducted a retrospective, descriptive and observational study with chart audits evaluating the anticoagulation indication and control for the preceding 1 year for each patient. Descriptive statistics included mean and standard deviation for quantitative data and frequencies for categorical data. Chi-square tests were used to analyse comparisons of categorical data and the student’s t-test for continuous variables. Two-tailed p-values less than 0.05 were considered significant. Results: TTR was poor for patients with AF and PHV (44.5% and 13.7% respectively). We identified older age, less frequent testing and high target ranges as significant factors associated with poorer outcomes. We demonstrated a high prevalence of adverse events (25.4%). Conclusion: Patients in this setting demonstrated poor quality of anticoagulation and had a high prevalence of adverse events.